A systematic review of the clinimetric properties of neuromotor assessments for preterm infants during the first year of life - Spittle, A.; Doyle, L.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2008)
This systematic review evaluates assessments used to discriminate, predict, or evaluate the motor development of preterm infants during the first year of life. Eighteen assessments were identified; nine met the inclusion criteria. The Alberta Infant Motor Scale (AIMS), Bayley Scale of Infant and Toddler Development - Version III, Peabody Developmental Motor Scales - Version 2, Test of Infant Motor Performance (TIMP), and Toddler and Infant Motor Examination have good discriminative validity when examined in large populations. The AIMS, Prechtl's Assessment of General Movements (GMs), Neuro Sensory Motor Development Assessment (NSMDA), and TIMP were designed for preterm infants and are able to detect more subtle changes in movement quality. The best predictive assessment tools are age dependent: GMs, the Movement Assessment of Infants, and TIMP are strongest in early infancy (age 4mo or less) and the AIMS and NSMDA are better at older ages (8-12mo). The TIMP is the only tool that has demonstrated a difference between groups in response to intervention in two randomized controlled trials. The AIMS, TIMP, and GMs demonstrated the highest levels of overall reliability (interrater and intrarater intraclass correlation coefficient or ?>0.85). Selection of motor assessment tools during the first year of life for infants born preterm will depend on the intended purpose of their use for discrimination, prediction, and/or evaluation. © 2008 Blackwell Publishing Ltd.